Identification of the essential protein domains for Mib2 function during the development of the Drosophila larval musculature and adult flight muscles - Domsch, Katrin (PLOS ONE, 2017)
The proper differentiation and maintenance of myofibers is fundamental to a functional musculature. Disruption of numerous mostly structural factors leads to perturbations of these processes. Among the limited number of known regulatory factors for these processes is Mind bomb2 (Mib2), a muscle-associated E3 ubiquitin ligase, which was previously established to be required for maintaining the integrity of larval muscles. In this study, we have examined the mechanistic aspects of Mib2 function by performing a detailed functional dissection of the Mib2 protein. We show that the ankyrin repeats, in its entirety, and the hitherto uncharacterized Mib-specific domains (MIB), are important for the major function of Mib2 in skeletal and visceral muscles in the Drosophila embryo. Furthermore, we characterize novel mib2 alleles that have arisen from a forward genetic screen aimed at identifying regulators of myogenesis. Two of these alleles are viable, but flightless hypomorphic mib2 mutants, and harbor missense mutations in the MIB domain and RING finger, respectively. Functional analysis of these new alleles, including in vivo imaging, demonstrates that Mib2 plays an additional important role in the development of adult thorax muscles, particularly in maintaining the larval templates for the dorsal longitudinal indirect flight muscles during metamorphosis.